2018
DOI: 10.1186/s12881-018-0586-9
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor gene polymorphisms and externalizing behaviors in children and adolescents

Abstract: BackgroundDopamine is involved in several cerebral physiological processes, and single nucleotide polymorphisms (SNP) in the dopamine D2 receptor gene (DRD2) have been associated with numerous neurological and mental disorders, including those involving alterations in cognitive and emotional processes.MethodsThe aim of this study was to evaluate the association between the SNPs c.957C > T (rs6277) and c.-585A > G (rs1799978) in the DRD2 gene and behavioral characteristics of children and adolescents based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The synonymous SNV rs6277T allele (957C > T; Pro319Pro) has shown a reduction in translation and mRNA stability, resulting in a decrease of up to 50 % in protein synthesis compared to the C allele. Furthermore, a significant association has been found between the T allele and genotypes CT and TT with defiant and oppositional problems, attention and hyperactivity ( Della Torre et al, 2018 ). In contrast to these findings, our study suggests no association between rs6277 and ADHD in Pakistani children.…”
Section: Discussionmentioning
confidence: 99%
“…The synonymous SNV rs6277T allele (957C > T; Pro319Pro) has shown a reduction in translation and mRNA stability, resulting in a decrease of up to 50 % in protein synthesis compared to the C allele. Furthermore, a significant association has been found between the T allele and genotypes CT and TT with defiant and oppositional problems, attention and hyperactivity ( Della Torre et al, 2018 ). In contrast to these findings, our study suggests no association between rs6277 and ADHD in Pakistani children.…”
Section: Discussionmentioning
confidence: 99%
“…Some single nucleotide polymorphisms (SNPs) in Apolipoprotein E (APOE), Brain Derived Neurotrophic Factor (BDNF), Glutathione S-Transferase Pi 1 (GSTP1) and Paraoxonase 1 (PON1) genes, have shown a possible role in pathways related with metal neurotoxicity (Gaynor et al 2009;Benke et al 2014;Trucco et al 2018;Della Torre et al 2018;Paes et al 2018;Cimino et al 2020;Lozano et al 2021;Treble-Barna et al 2022). For instance, a Taiwanese study (Ng et al 2015) observed that children's carriers of APOE ε4 showed a higher risk of internalizing and externalizing problems with increasing mercury at the age of two years.…”
Section: Introductionmentioning
confidence: 99%
“…But, the current evidence is inadequate, for the reason that sparseness of data or inconsistencies among these reported investigations. This meta-analysis was conducted to assess whether the null genotype of GSTM1/GSTT1 and the GSTP1 A/G gene polymorphism are associated with RCC susceptibility by ethnicity, and whether there is an association between the null genotype of GSTM1/GSTT1 and clinical TNM stages in patients with RCC by ethnicity, due to the fact that the genotype distributions of the different populations might differ from each other [ 27 , 28 ]. We also evaluated the publication bias for the relationship between the GSTM1 -null genotype, GSTT1 -null genotype, dual GSTM1/GSTT1 -null genotype, and GSTP1 A/G gene polymorphism and RCC risk for the overall population.…”
Section: Introductionmentioning
confidence: 99%